2016
DOI: 10.1016/j.neuropharm.2016.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Selective chemical genetic inhibition of protein kinase C epsilon reduces ethanol consumption in mice

Abstract: Reducing expression or inhibiting translocation of protein kinase C epsilon (PKCε) prolongs ethanol intoxication and decreases ethanol consumption in mice. However, we do not know if this phenotype is due to reduced PKCε kinase activity or to impairment of kinase-independent functions. In this study, we used a chemical-genetic strategy to determine whether a potent and highly selective inhibitor of PKCε catalytic activity reduces ethanol consumption. We generated ATP analog-specific PKCε (AS-PKCε) knock-in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Recently we generated mutant mice that carry an ATP analog-specific gatekeeper mutation in the purine-binding site of PKCε ( AS -PKCε mice) and found that administration of the selective AS -kinase inhibitor 1-NA-PP1 reduces their ethanol intake (9). These results predict that small-molecule inhibitors of PKCε should decrease ethanol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we generated mutant mice that carry an ATP analog-specific gatekeeper mutation in the purine-binding site of PKCε ( AS -PKCε mice) and found that administration of the selective AS -kinase inhibitor 1-NA-PP1 reduces their ethanol intake (9). These results predict that small-molecule inhibitors of PKCε should decrease ethanol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Studies employing PKCε-null mutant mice reported these mice to consume significantly less ethanol (Hodge et al, 1999 ) and even to exhibit an increased aversion to ethanol (Newton and Messing, 2007 ). More recently, selective chemical genetic inhibition of PKCε catalytic activity has proven successful in decreasing ethanol consumption in mice (Maiya et al, 2016 ). Biochemical studies have revealed PKCε to modulate ethanol consumption behavior by decreasing inhibitory GABAergic neurotransmission through the phosphorylation of the GABA A ⋎2 subunit at S327 (Qi et al, 2007 ) and phosphorylation of the N-ethylmaleimide sensitive factor at S460 and T461 (Chou et al, 2010 ).…”
Section: Pkcε In Ethanol-induced Neurobehavioral Changesmentioning
confidence: 99%
“…PKCε is considered to mediate an ethanol-tolerant phenotype because of its interactions with receptors such as gamma aminobutyric acid (GABA A ) (Poisbeau et al, 1999 ) and metabotropic glutamate receptor subtype 5 (mGlu5) (Olive et al, 2005 ; Kumar et al, 2017 ) in CNS. Null mutations of PKCε have been found to attenuate ethanol drinking behavior in rodents (Lesscher et al, 2009 ; Maiya et al, 2016 ), and prolonged ethanol exposure significantly increases PKCε expression (Messing et al, 1991 ; Coe et al, 1996 ; Kumar et al, 2016 ). Thus, there is an incentive for developing potent, selective, and brain-penetrant PKCε inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Further, male PKCε −/− mice consume less alcohol and nicotine compared with their wild‐type (WT) littermates and show enhanced sensitivity to the sedative properties of alcohol 15,16 . Recent studies have shown that targeting PKCε with small molecule inhibitors or conditional genetic inhibition can reduce alcohol consumption in mice, indicating that PKCε may be a promising target for pharmacotherapies to reduce alcohol and/or nicotine consumption 17,18 . However, the majority of studies on the relationship between PKCε, nAChRs, and addictive behaviors have used only male mice, hindering the ability to translate preclinical research into a clinical setting.…”
Section: Introductionmentioning
confidence: 99%